Coronary Graft Failure State of the Art - Ţintoiu, Ion C.; Underwood, Malcolm John; Cook, Stephane Pierre; Kitabata, Hironori; Abbas, Aamer (Springer International Publishing : Imprint: Springer, 2016)
This book evaluates the current state of knowledge regarding coronary graft failure. It reviews how graft failure can be caused by many factors including the complexity of multiple coronary vessel lesions with surgical revascularization, numerous pathogenic mechanisms of arterial or venous graft dysfunction in the presence of other comorbidities (diabetes mellitus, hypertension and dyslipidemia), and the development of intra-graft atherosclerosis process or distally to the graft. Coronary Graft Failure represents the accumulation of data on pathophysiological mechanisms of maintenance and progression of this pathology, while quantifying of diagnostic methods and the value of each in part for the best approach strategy for planning of recurrent revascularization (redo). It also evaluates the therapeutic solutions available for graft revascularization. As such, it will be a vital reference for all involved in the management of patients undergoing graft restenosis whether interventional or surgical. .